The lockdown chronicles 19 Malaysian voices - Shireen Zainudin; Viji Krishnamoorthy (Media Master Publishing Sdn. Bhd., 2020)
Nineteen stories by Malaysians that bring together reflections of 'these strange, unsettling, totally unprecedented times' of the Covid-19 pandemic. As the editors write, 'everyone was journeying uniquely and inwardly' during the long weeks of enforced isolation. The different voices here offer very diverse fictions of how those days were. In addition to the two editors, the writers are: Clarice Chan, Alasdair Clayre, Pauline Fan, Candice Foong, Marc de Faoite, Mwaffaq Al-Hajjar, Renie Leng, Shida Mahadi, Sujatha Sekhar Naik, Sarena Salleh, Ranjit Singh, Michelle Soin, Nur Suraya, Pete Teo, Su Ming Tham, Lavina Valiram, Hartini Zainudin, Anurendra Jegadeva and Maya Ranjit Singh.